Predictive Effect of EPS Results on Prostate Cancer Detection in Patients with High PSA Values - Yariş, Mehmet (Cerrahpaşa Medical Journal, 2022)
Background: The aim of this study was to evaluate prostate cancer detection rates with the expressed prostatic secretion test to avoid unnecessary prostate biopsy procedures and increase prostate-specific antigen reliability in patients with high prostate-specific antigen values. Methods: Ninety-three expressed prostatic secretion-positive and 97 expressed prostatic secretion-negative patients with serum prostate-specific antigen levels of 2.5 ng/mL were included in this retrospective study. The diagnostic evaluation included a detailed history and physical examination, digital rectal examination, urinalysis, urine culture, and the expressed prostatic secretion test. Transrectal ultrasonography was used both to measure the prostate volume and obtain 12-core prostate biopsies. Results: In our study, the mean age of the 190 patients was 62.59 ± 8.47 years. The mean prostate-specific antigen value of the patients was 5.25 ± 1.7 ng/mL, the mean International Prostatism Symptom Score was 11.8 ± 7, and the mean prostatic volume was 47.5 ± 20 mL. Prostate cancer was detected in 10 patients in the expressed prostatic secretion-positive group and 20 patients in the expressed prostatic secretion-negative group (P = .034). Conclusion: In the expressed prostatic secretion-negative group, the rate of prostate cancer detection was statistically significantly higher. Cite this article as: Yariş M. Predictive effect of EPS results on prostate cancer detection in patients with high PSA values. Cerrahpaşa Med J. 2022;46(2):126-128.